Analyzing strategic entrepreneurial choices in agriculture—Empirical evidence from Germany - Viktoria Graskemper; Xiaohua Yu; Jan-Henning Feil (Agribusiness, 2021)
Entrepreneurship in agriculture is a phenomenon that is growing in importance with the changing framework conditions for agricultural production and has led to heterogeneity in farm business development paths. To understand this phenomenon better, a classification scheme for strategic entrepreneurial choices in agriculture is developed for family farmers. The choices that are scrutinized are reduction, continuation, expansion, diversification, and the dual strategy of expansion and diversification. Each farmer is uniquely assigned to one of these choice classes according to their implemented entrepreneurial activities. Determinants influencing these choices are investigated with a multinomial logit model. The data are derived from a quantitative survey among German farmers (N0.167em=0.167em745). Strong effects are observable within the area of personal factors; creativity and risk affinity benefit entrepreneurial strategies connected with diversification. Farmers with a third-level education qualification are less likely to follow expansion strategies, and those with off-farm employment and risk-averse farmers mainly choose a reduction strategy. Family involvement, especially the farmer's spouse, proves to have stabilizing and even enhancing effects on certain strategies. Implications for policymakers and actors within the agricultural sector can thus be derived.
Keywords: 630; entrepreneurship; farming strategy; multinomial logit model; strategic entrepreneurial choices